On the automorphism group of the algebra of the scalar upper triangular matrices - Özkan, Özkay (Gebze Teknik Üniversitesi, Lisansüstü Eğitim Enstitüsü, 2020)
Birimli ve değişmeli bir R halkası üzerinde, kesin üst üçgensel n x n matris cebirleri, n > 1 bir tamsayı olmak üzere Nn(R) ile gösterilir. I birim matris, a?R, A?Nn(R) olmak üzere a I + A biçiminde tanımlı tüm elemanların oluşturduğu küme, üst üçgensel matris cebri Tn(R)'ın bir alt cebridir. Bu alt cebire skaler üst üçgensel matris cebirleri denir ve bu cebir STn(R) ile gösterilir. Bu tezde, STn(R) cebrinin tüm otomorfizmaları araştırılmıştır. Nn (R) cebrinin otomorfizmaları STn(R) cebrinin otomorfizmalarına genişletilmiş ve STn(R) cebrinin tüm otomorfizmaları sınıflandırılmıştır. STn(R) cebrinin otomorfizmalarının Tn(R) cebrinin otomorfizmalarına her koşulda genişletilemeyeceği ispatlanmıştır.

For a commutative ring R with unity, the R-algebra of strictly upper triangular n x n matrices over R is denoted by Nn(R), where n is a positive integer greater than 1. For the identity matrix I, a?R, A?Nn(R), the set of all elements aI+A is defined as the scalar upper triangular matrix algebra STn(R) which is a subalgebra of the upper triangular matrix algebra Tn(R). In this thesis, we investigate the R-algebra automorphisms of STn (R). We extend the automorphisms of Nn (R) to STn(R) and classify all the automorphisms of STn(R). We prove that there exist some automorphisms of STn(R) which cannot be extended to any automorphism of Tn(R).
Skaler üst üçgensel matris cebirlerinin otomorfizma grupları
Keywords: Matematik; Mathematics